2018
DOI: 10.1177/1742395318792063
|View full text |Cite
|
Sign up to set email alerts
|

Pre-post effectiveness evaluation of Chronic Disease Self-Management Program (CDSMP) participation on health, well-being and health service utilization

Abstract: Objectives The Chronic Disease Self-Management Program (CDSMP) is a standardized self-management intervention for patients with various chronic diseases. CDSMP provides self-management skills to enhance patient health, well-being, and coping skills. The present study evaluates the effectiveness of CDSMP delivered in routine clinical services on health, health behaviors and healthcare utilization in patients with various chronic illnesses. Methods A pragmatic single group pre-post design evaluated the effective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 32 publications
2
22
0
2
Order By: Relevance
“…The effectiveness of the CDSMP has been demonstrated in studies across age groups and diverse cultural and ethnic backgrounds [23], including improvements in self-efficacy [17,18,[25][26][27], health behaviour (i.e., exercise frequency, symptom management, communication with healthcare providers) [27][28][29], health status (i.e., level of self-reported health, health distress, disability, fatigue, quality of life) [25,[28][29][30][31], and health service utilisation (reduction in emergency presentations and hospitalisations) [24,29,31]. Qualitative evaluations suggest that CDSMP is acceptable to participants, and the group-based modality helps enhance participation, social connectedness, coping, and the acceptance of chronic condition(s) amongst participants [20,[32][33][34].…”
Section: Interventionmentioning
confidence: 99%
“…The effectiveness of the CDSMP has been demonstrated in studies across age groups and diverse cultural and ethnic backgrounds [23], including improvements in self-efficacy [17,18,[25][26][27], health behaviour (i.e., exercise frequency, symptom management, communication with healthcare providers) [27][28][29], health status (i.e., level of self-reported health, health distress, disability, fatigue, quality of life) [25,[28][29][30][31], and health service utilisation (reduction in emergency presentations and hospitalisations) [24,29,31]. Qualitative evaluations suggest that CDSMP is acceptable to participants, and the group-based modality helps enhance participation, social connectedness, coping, and the acceptance of chronic condition(s) amongst participants [20,[32][33][34].…”
Section: Interventionmentioning
confidence: 99%
“…4,5 Large amount of evidence supported the effectiveness of the CDSMP in improving physical and psychological well-being, 6,7 health-related quality of life, 8 medication utilization, 9 and communication with health professionals. 8 Moreover, healthcarerelated cost savings were demonstrated in several studies in terms of reduction in visits to general practitioner, admission to the emergency department and besides lower frequency and shorter duration of hospitalization. 10,11 Although it has been clearly demonstrated that CDSMP led to better health outcomes, an important issue is identifying whether baseline participants' characteristics are able to predict better clinical outcomes after attending this intervention.…”
Section: Introductionmentioning
confidence: 99%
“…It is also suggested that enough financial support for health promotion may lead to improved health conditions and reduced unmet needs. Another study examining pre-post effectiveness of evaluation of chronic disease management yielded positive results for patients with fewer visits to the clinic [18]. However, there are insufficient studies that examine the relationship of an improved lifestyle to unmet needs among patients with chronic diseases.…”
Section: Introductionmentioning
confidence: 99%